Characterization of the Spatial and Temporal Expression of Two Soybean miRNAs Identifies SCL6 as a Novel Regulator of Soybean Nodulation - Hossain, Md Shakhawat; Hoang, Nhung T.; Yan, Zhe; Tóth, Katalin; Meyers, Blake C.; Stacey, Gary (Frontiers in Plant Science, 2019)
• MicroRNAs (miRNAs) control expression of endogenous target genes through transcript cleavage or translational inhibition. Legume plants can form a specialized organ, the nodule, through interaction with nitrogen fixing soil bacteria. To understand the regulatory roles of miRNAs in the nodulation process, we functionally validated gma-miR171o and gma-miR171q and their target genes in soybean. • These two miRNA sequences are identical in sequence but their miRNA genes are divergent and show unique, tissue-specific, expression patterns. The expression levels of the two miRNAs are negatively correlated with that of their target genes. Ectopic expression of these miRNAs in transgenic hairy roots resulted in a significant reduction in nodule formation. Both gma-miR171o and gma-miR171q target members of the GRAS transcription factor superfamily, namely GmSCL-6 and GmNSP2. Transient interaction of miRNAs and their target genes in tobacco cells further confirmed their cleavage activity. The results suggest that gma-miR171o and gma-miR171q regulate GmSCL-6 and GmNSP2, which, in turn, influence expression of the Nodule inception (NIN), Early Nodulin 40 (ENOD40) and Ethylene Response Factor Required for Nodulation (ERN) genes during the B. japonicum-soybean nodulation process. • Collectively, our data suggest a role for two miRNAs, gma-miR171o and gma-miR171q, in regulating the spatial and temporal aspects of soybean nodulation.